Kajian Hukum dalam Rehabilitasi Tindak Pidana Narkotika terhadap Pelaku Penyalahgunaan bagi Dirinya Sendiri - Ardiansyah Firdaus; Alip Rahman; Anom Sutrisno (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the legal regulations for perpetrators of self-abuse of narcotics who meet the rehabilitation criteria and the judge's legal considerations in Decision Number 372/Pid.Sus/2024/PN.Sbr. The research method used is normative juridical with a statutory regulatory approach, a case approach and a conceptual approach. The results of the study indicate that rehabilitation has been regulated in Law Number 35 of 2009 concerning Narcotics, Supreme Court Circular Letter Number 4 of 2010 and Joint Regulation of 2014. The decision has correctly applied Article 127 paragraph (1) letter a, but the judge's considerations have not comprehensively explained the reasons for not implementing rehabilitation, so that the orientation of punishment still emphasizes imprisonment rather than a rehabilitative approach.